2003
DOI: 10.1074/jbc.m305841200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Docosanoids Inhibit Brain Ischemia-Reperfusion-mediated Leukocyte Infiltration and Pro-inflammatory Gene Expression

Abstract: Ischemic stroke triggers lipid peroxidation and neuronal injury. Docosahexaenoic acid released from membrane phospholipids during brain ischemia is a major source of lipid peroxides. Leukocyte infiltration and pro-inflammatory gene expression also contribute to stroke damage. In this study using lipidomic analysis, we have identified stereospecific messengers from docosahexaenoate-oxygenation pathways in a mouse stroke model. Aspirin, widely used to prevent cerebrovascular disease, activates an additional path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
772
1
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 746 publications
(804 citation statements)
references
References 34 publications
21
772
1
10
Order By: Relevance
“…More recently, DHA-derived mediators D-series resolvins, docosatrienes and neuroprotectins, also produced by cyclooxygenase-2 and lipoxygenase under some conditions, have been identified that also appear to be antiinflammatory and inflammation resolving Marcheselli et al 2003;Mukherjee et al 2004). Only two studies in the current overview provide direct comparison of the effects of EPA and DHA.…”
Section: Discussionmentioning
confidence: 97%
“…More recently, DHA-derived mediators D-series resolvins, docosatrienes and neuroprotectins, also produced by cyclooxygenase-2 and lipoxygenase under some conditions, have been identified that also appear to be antiinflammatory and inflammation resolving Marcheselli et al 2003;Mukherjee et al 2004). Only two studies in the current overview provide direct comparison of the effects of EPA and DHA.…”
Section: Discussionmentioning
confidence: 97%
“…Platelet-rich supernatant was further centrifuged at 1600 ϫ g for 15 minutes to collect platelets. Cell deposit was used to isolate PMNs by density gradient centrifugation using Histopaque 1.077 cell separation medium (Sigma-Aldrich 23 Samples and standards of lipid mediators were handled under dimmed light, stored at Ϫ80°C in vials purged with nitrogen gas and sealed tightly. Aqueous solutions of DHA and DHA derivatives were freshly prepared (ϳ4°C) immediately before use.…”
Section: Cell Culturesmentioning
confidence: 99%
“…In experimental stroke, endogenous NPD1 synthesis was found to be upregulated during the initial eight hours of reperfusion [7]. When this lipid mediator was infused into the brain during ischemia-reperfusion, neuroprotective bioactivity was revealed [7].…”
Section: Experimental Strokementioning
confidence: 99%
“…Since lipoxygenase inhibitors were found to block this synthesis, an enzymatic process catalyzed by a lipoxygenase was implied [6] and the name "docosanoids" was suggested because they are derived from the 22C DHA. Upon the development of lipidomic analysis based on liquid chromatography, photodiode array, electrospray ionization, and tandem mass spectrometry (LC-PDA-ESI-MS-MS-based lipidomic analysis), a collaboration between the group of Charles Serhan (Harvard Medical School, http://hms.harvard.edu/hms/home.asp) and our group identified oxygenation pathways for the synthesis of the docosanoid neuroprotectin D1 (NPD1) and its bioactivity during brain ischemia-reperfusion [7] and in retinal pigment epithelial (RPE) cells challenged by oxidative stress [8]. We suggested the name 'neuroprotectin D1' [8] based upon its neuroprotective bioactivity in oxidatively stressed RPE cells and brain and its potent ability to inactivate pro-apoptotic and pro-inflammatory signaling.…”
Section: Introductionmentioning
confidence: 99%